2014
DOI: 10.1007/s10637-014-0189-z
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of sulforaphane-rich broccoli sprout extracts in men with recurrent prostate cancer

Abstract: Diets high in cruciferous vegetables are associated with lower risk of incidence of prostate cancer, including aggressive forms of this disease. Human intervention studies with cruciferous vegetable-rich diets also demonstrate modulation of gene expression in important pathways in prostate cells. Sulforaphane is a constituent of these foods postulated to harbor the anti-neoplastic activity based on multiple tumor models. Our own work demonstrates that sulforaphane inhibits AR signaling in prostate cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
133
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 32 publications
1
133
0
1
Order By: Relevance
“…The fundamental role of epigenetic mechanisms in the regulation of gene expression and epigenetic aberrations implicated in various pathologies itself underlines the importance of compounds targeting them. It is much more challenging than it seems to develop dietary phytochemicals as effective chemopreventive and/or chemotherapeutic agents despite their widespread recognition and acceptance as evident from a large number of research publications [204258]. There is still insufficient preclinical and clinical data published on the epigenetic changes induced by some of the dietary polyphenols, which remains a challenge and limitation, of the current data to acquire better insight on the molecular mechanisms responsible for these effects.…”
Section: 0 Conclusion Limitation and Future Directionmentioning
confidence: 99%
“…The fundamental role of epigenetic mechanisms in the regulation of gene expression and epigenetic aberrations implicated in various pathologies itself underlines the importance of compounds targeting them. It is much more challenging than it seems to develop dietary phytochemicals as effective chemopreventive and/or chemotherapeutic agents despite their widespread recognition and acceptance as evident from a large number of research publications [204258]. There is still insufficient preclinical and clinical data published on the epigenetic changes induced by some of the dietary polyphenols, which remains a challenge and limitation, of the current data to acquire better insight on the molecular mechanisms responsible for these effects.…”
Section: 0 Conclusion Limitation and Future Directionmentioning
confidence: 99%
“…However, the intervention increased PSADT by 86% and mean changes in PSA after 6 months was significantly lower in the treatment group [88]. Further, consumption of 200 μmoles/day sulforaphane-rich broccoli sprout extract for 20 weeks by PCA patients with biochemical recurrence led to a < 50% decline in PSA in 7 out of 20 patients and increased PSADT with one patient showing ≥ 50% decline in PSA [89]. Additionally, consumption of 400 g broccoli by HGPIN patients for a year caused significant changes in androgen, TGF-β, IGF and EGF signaling and the mechanism suggested was a covalent interaction of sulforaphane with insulin, TGF-β and EGF peptides to form thiourea [90].…”
Section: Whole Vs Isolated Compound Entitiesmentioning
confidence: 99%
“…These clinical trials are currently in the early phases and have established safety and feasibility of oral administration of broccoli-derived constituents over long periods (up to 1 year) in a wide variety of settings ranging from pre-cancerous prostate conditions (high-grade PIN) to metastatic prostate cancer [5456]. Two trials recently reported the role of SFN in biochemical [prostate specific antigen (PSA)] recurrence in patients with prostate cancer after definitive surgery or radiation therapy.…”
Section: Clinical Trials In Humans Using Sulforaphanementioning
confidence: 99%
“…These trials are summarized below. In a single arm pilot study, Alumkal et al treated patients with biochemical recurrence of prostate cancer with 200 μmol of SFN for up to 20 weeks [56]. Eighteen of the twenty patients enrolled completed the pre-planned 20 weeks of treatment.…”
Section: Clinical Trials In Humans Using Sulforaphanementioning
confidence: 99%
See 1 more Smart Citation